Membangun Keterlibatan Orang Tua Dalam Pendidikan Anak - Nafilatur Rohmah (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2018)
This study aims to reveal the efforts in improving the parental involvement in children’s education along with supporting factors and inhibiting factors. The research method which is used is qualitative method that is presented descriptively. The result of the study indicates that the effort which are presented are as follows: (1) involving parents in the Commemoration of Islamic Holidays and Commemoration of National Holidays: (2) holding parenting activities; (3) mutual cooperation to build school; (4) meeting concern problem of school; (5) meeting in taking report purpose. Supporting factors come from the principal, figures or elders of the school, and teachers. The inhibiting factor comes from parents.